Survey of robotic manipulation studies intending practical applications in real environments -object recognition, soft robot hand, and challenge program and benchmarking-. (18th October 2017) - Watanabe, Tetsuyou; Yamazaki, Kimitoshi; Yokokohji, Yasuyoshi
Abstract : Aiming at accelerating the creation of new techniques on dexterous robotic manipulations, this paper surveyed the recent results on object recognition, soft robotic hands, and benchmarks and challenge/competition programs. The former two topics construct the elemental components of the new technologies on robotic manipulations, while the last one is a key for proceeding the creation and realization of the actual robotic manipulations with the new techniques. With these surveys, we will reveal the solved and unsolved issues for the next step to realize robotic dexterous manipulation systems comparable to human being.